Illicit financial flows : the economy of illicit trade in West Africa - Organisation for Economic Co-operation and Development (OECD, 2018)
Summary.
Keywords: salakauppa : Länsi-Afrikka; salakuljetus : Länsi-Afrikka; kansainvälinen kauppa : Länsi-Afrikka; ulkomaankauppa : Länsi-Afrikka; rajakauppa : Länsi-Afrikka; lahjonta : Länsi-Afrikka; järjestäytynyt rikollisuus : Länsi-Afrikka; rikollisuuden ehkäiseminen : Länsi-Afrikka